Mask-wearing and respiratory infection in healthcare workers in Beijing, China - Yang,Peng (2011)
OBJECTIVES: The aim of the study was to determine rates of mask-wearing, of respiratory infection and the factors associated with mask-wearing and of respiratory infection in healthcare workers (HCWs) in Beijing during the winter of 2007/2008. METHODS: We conducted a survey of 400 HCWs working in eight hospitals in Beijing by face to face interview using a standardized questionnaire. RESULTS: We found that 280/400 (70.0%) of HCWs were compliant with mask-wearing while in contact with patients. Respiratory infection occurred in 238/400 (59.5%) subjects from November, 2007 through February, 2008. Respiratory infection was higher among females (odds ratio [OR], 2.00 [95% confidence interval CI, 1.16-3.49]) and staff working in larger hospitals (OR, 1.72 [95% CI, 1.092.72]), but was lower among subjects with seasonal influenza vaccination (OR, 0.46 [95% CI, 0.280.76]), wearing medical masks (reference: cotton-yarn; OR, 0.60 [95% CI, 0.39-0.91]) or with good mask-wearing adherence (OR, 0.60 [95% CI, 0.37-0.98]). The risk of respiratory infection of HCWs working in low risk areas was similar to that of HCWs in high risk area. CONCLUSION: Our data suggest that female HCWs and staffs working in larger hospitals are the focus of prevention and control of respiratory infection in Beijing hospitals. Mask-wearing and seasonal influenza vaccination are protective for respiratory infection in HCWs; the protective efficacy of medical masks is better than that of cotton yarn ones; respiratory infection of HCWs working in low risk areas should also be given attention.